Diagnostic value of detailed metabolic pathway investigations in two cases of phaeochromocytoma with minimal increase in total catecholamine output. Issue 5 (September 1966) - Brown, J. J.; Ruthven, C. R. J.; Sandler, M.
Abstract : Two patients with phaeochromocytoma having atypical biochemical features are described. Total catecholamine excretion was normal in one and only slightly raised in the other; both had a diagnostic rise in output of metadrenaline and 4-hydroxy-3-methoxymandelic acid whilst 4-hydroxy-3-methoxyphenylglycol excretion was increased in one of them. During hypertensive attacks adrenaline excretion became greater than that of noradrenaline. The diagnostic usefulness of separate adrenaline and noradrenaline estimations in addition to catecholamine metabolite assay is discussed. A lack of relationship between tumour catecholamine content and urinary catecholamine output is emphasized.